Medea and the politics of (theatrical) location - Čale Feldman, Lada (2004)
The lecture discusses the media treatment of the role of Medea played by the exiled Croatian actress Mira Furlan on the occasion of her highly politically charged "come-back" to Croatia. Questioning the controversy of this myth for the feminist politics, the lecture further juxtaposes this event and the postdramatic treatment of this myth by a young Croatian woman playwright Ivana Sajko.
Projekt MZOS
Projekt MZOS
ENG